Assessment of osteoarthritic features in the thumb base with the newly developed OMERACT magnetic resonance imaging scoring system is a valid addition to standard radiography. Issue 3 (March 2019) - van Beest, S.; Kroon, F.P.B.; Kroon, H.M.; Damman, W.; Liu, R.; Bloem, J.L.; Reijnierse, M.; Kloppenburg, M.
Summary: Objective: To investigate the construct validity of the new thumb base OA magnetic resonance imaging (MRI) scoring system (TOMS) by comparing TOMS scores with radiographic scores in patients with primary hand OA. Design: In 200 patients (83.5% women, mean (SD) age 61.0 (8.4) years), postero-anterior radiographs and MR scans (1.5 T) of the right first carpometacarpal (CMC-1) and scaphotrapeziotrapezoid (STT) joints, were scored using the OARSI atlas and TOMS, respectively. The distributions of the TOMS scores (specified in results section) were stratified for the OARSI scores of corresponding radiographic features and investigated using boxplots and non-parametric tests. Furthermore, Spearman's rank or Phi correlation coefficients ( ρ / φ ) were calculated. Results: For all features, especially for erosions and osteophytes, the prevalence found with MRI was higher than with radiography. TOMS osteophyte and cartilage loss scores differed statistically significant between corresponding OARSI scores in CMC-1 (0 vs 1; 1 vs 2). TOMS scores were positively correlated with radiographic scores in CMC-1 for osteophytes (coefficient [95% confidence interval], ρ  = 0.75 [0.69; 0.81]), cartilage loss/joint space narrowing ( ρ  = 0.70 [0.62; 0.76]), subchondral bone defects (SBDs)/erosion-cyst ( ρ  = 0.41 [0.29; 0.52]), bone marrow lesions (BMLs)/subchondral sclerosis ( ρ  = 0.65 [0.56; 0.73]) and subluxation ( φ  = 0.65 [0.57; 0.73]); and in STT for osteophytes ( ρ  = 0.30 [0.17; 0.42]) and cartilage loss/joint space narrowing ( ρ  = 0.53 [0.42; 0.62]). Conclusions: In patients with hand OA, TOMS scores positively correlated with radiographic scores, indicating good construct validity. However, the prevalence of features on MR images was higher compared to radiographs, suggesting that TOMS might be more sensitive than radiography. The clinical meaning of these extra MR detected cases is currently still unknown.